Linear optimization model of urban areas’ operating efficiency - Tanczos, Katalin; Torok, Arpad (Transport, 2007)
The efficiency of urban transportation is getting more and more important because of the increasing rate of mobility demand. To plan, control and organize urban transportation in the most efficient way, we also need to consider the aspects of land use. To handle both of the mentioned urban planning areas together, we shall develop models, which are able to pay attention to all of their restrictive factors in the most simple way. It is a possible solution to simulate the urban area through a linear programming model.First Published Online: 27 Oct 2010